2008
DOI: 10.1007/s11605-008-0504-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Laparoscopic Cholecystectomy for Severe Acute Cholecystitis

Abstract: The aim of this study was to evaluate the surgical outcomes of laparoscopic cholecystectomy (LC) in patients who were diagnosed with severe acute cholecystitis (SAC) and to clarify the useful treatment modalities of SAC. Of 112 patients who presented SAC, we selected 99 patients and divided them into 3 groups: 37 patients who underwent preoperative percutaneous transhepatic gallbladder drainage (PTGBD; group 1), 62 patients with SAC but not indicated for PTGBD (group 2), and 59 patients with acute and chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
2
15
1
1
Order By: Relevance
“…However, older age and higher comorbidities were found in the PC group. Another study showed that PC had a shorter operation time and shorter postoperative hospital stay than emergency cholecystectomy [20]. In our study, the mortality rate was higher in the elderly group but was not statistically significant.…”
Section: Discussioncontrasting
confidence: 61%
“…However, older age and higher comorbidities were found in the PC group. Another study showed that PC had a shorter operation time and shorter postoperative hospital stay than emergency cholecystectomy [20]. In our study, the mortality rate was higher in the elderly group but was not statistically significant.…”
Section: Discussioncontrasting
confidence: 61%
“…The mortality rate was significantly higher in the primary open approach but not in the converted group. Practically, AC remains a severe and potentially lethal disease [27,29], especially in elderly and high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, PTGBD may not increase postoperative infectious complications after LC, according to results of our study and published papers. 25,26 It is still unclear whether PTGBD before LC improves surgical outcomes, although several reports have already been published to support its effectiveness. 2628 …”
Section: Discussionmentioning
confidence: 99%